(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the price and nutritional characterization of foods offered in fast food apps in the city of Teresina-PI in Covid-19. Was performed a cross-sectional study of descriptive bibliographic nature with a quantitative and qualitative approach. Three applications named A, B, and C were selected. Data collection was carried out during three (3) days and took place from 7 pm to 10 pm. The data were recorded in a spreadsheet in the Excel software, the Stat D+ program was used for statistical treatment, and the presentation of the results was performed using graphics and tables in the Word software. The app with the lowest average price was APP-C (26.68 reais). 148 establishments were found, of which 317 preparations and 1,899 ingredients were collected. There was a high demand for food offerings of low nutritional quality, rich in simple carbohydrates, fats and sodium. It is concluded that the analyzed applications do not include nutritional recommendations and caloric intake in their offers, thus verifying, negligence in some significant dietary recommendations, such as including vegetables, fruits and legumes in the preparations.